O contexto da responsabilidade civil frente às construções irregulares em áreas de proteção ambiental - Souza, Ana Maria Alves de (2023)
As the centuries passed, humanity improved its rules, including the right to property and environmental law. These institutes, due to their interconnected nature, in which human beings, due to their consuming action on natural resources, have the capacity to cause impacts on the environment, requiring effective regulation and supervision. Thus, in relation to environmental devices in confrontation with human needs, the need for housing opened up hypotheses of irregular construction, which can occur in any ecosystem; but, at present, they focus on Environmental Protection Areas. In this regard, this work sought to answer the following question: What are the impacts caused by irregular constructions in Environmental Protection Areas, with regard to the civil liability disseminated in the specific law? To respond, the methodology adopted used methods and techniques based on the use of extensive bibliographical references, such as legislation, official documents, and related literature, as well as the use of qualitative and descriptive analysis. After carrying out this study, it is concluded that the legislation in force, although it has a large material extension, becomes ineffective when there is no supervision and effective application. Furthermore, the use of permaculture becomes an effective mitigating measure to minimize negative impacts in irregular constructions, assisting in government public policies.